A new distance measure based on the weighted induced method and its application to Pythagorean fuzzy multiple attribute group decision making. Issue 7 (1st March 2019) - Yu, Liping; Zeng, Shouzhen; Merigó, José M.; Zhang, Chonghui
Abstract: This paper investigates a novel induced ordered weighted averaging (IOWA) distance operator and its application in Pythagorean fuzzy (PF) multiattribute group decision making (MAGDM). First, a new induced aggregated distance operator named the weighted IOWA distance (WIOWAD) operator is developed, which differs from the existing methods in that it considers the dual roles of the order‐inducing variables at the same time. In other words, in addition to inducing the order of the arguments, the order‐inducing variables of the WIOWAD operator also plays an important role in moderating the associated weight vector. Some useful properties and different families of the WIOWAD are also discussed. Then, an extension of the WIOWAD within the PF situation is presented, thus obtaining the PFWIOWAD operator. Furthermore, a MAGDM method based on the PFWIOWAD is introduced. Finally, the practicality and effectiveness of proposed approach are illustrated in a research and development project selection problem.